Pengaruh Model Problem Based Learning (PBL) terhadap Sikap Peduli Lingkungan pada Mata Pelajaran PKn Siswa Kelas II SD 1 Tumpangkrasak - Zerra Puspita Angellina; Deva Putri Rahmawati; Riska Zeli Wijayanti; Syahreza Pahlevi Susanto (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Environmental care is an important character trait that should be developed from the elementary school level. Observations conducted in Grade II at SD 1 Tumpangkrasak revealed that students' environmental care attitudes were relatively low, indicating the need for a learning model that actively engages students in the learning process. This study aimed to examine the effect of the Problem-Based Learning (PBL) model on students' environmental care attitudes in the Civic Education (Pancasila and Civic Education/PPKn) subject among second-grade students at SD 1 Tumpangkrasak. The study employed a quantitative approach using an experimental method with a One-Group Pretest–Posttest Design. The sample consisted of 16 students selected through total sampling (saturated sampling). Data were collected using questionnaires, observations, and documentation, and were analyzed using descriptive statistics and the Paired Sample t-test. The results showed that the mean score of students' environmental care attitudes increased from 68.31 in the pretest to 84.50 in the posttest. The hypothesis test yielded a significance value of 0.000, indicating that the Problem-Based Learning model had a statistically significant effect on students' environmental care attitudes. Therefore, the Problem-Based Learning model can be considered an effective alternative instructional approach for improving environmental care attitudes in Civic Education at the elementary school level.